Preparation method of aluminum alloy surface corrosion-resistant film layer and aluminum alloy surface corrosion-resistant film layer

Through two steps to seal the hole technology, the use of ammonium and nano -emulsion to form a dense transparent hydrophobic film on the surface of the aluminum alloy to solve the problem that existing technologies cannot take into account light transparency and corrosion resistance, significantly improved the resistance of aluminum alloy electronic products Corrosion performance and stability.

CN119352128AInactive Publication Date: 2025-01-24XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411898719.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing anodizing and its sealing process cannot achieve both bright, transparent and corrosion resistance on the surface of aluminum alloy electronic products, resulting in limited product stability and user experience.

Method used

Use two-step holes to seal the holes, first use the ammonium ammonium ammonium and aluminum aluminum reaction to generate aluminum oxyxane, and then use lithium siliconicate and γ-shrinking glycelacelcelaceroxyl oxygen oxygne. The emulsion seal the holes to form a dense transparent hydrophobic film.

Benefits of technology

It significantly improves the sweat resistance of aluminum alloy electronic products, maintains the bright and transparent appearance of the surface, and improves the stability and application range of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352128A_ABST
    Figure CN119352128A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a preparation method of a corrosion-resistant film layer on the surface of an aluminum alloy and the corrosion-resistant film layer on the surface of the aluminum alloy, and relates to the technical field of surfaces.The preparation method comprises the steps that the aluminum alloy is pretreated, and the pretreated aluminum alloy is obtained; the pretreatment comprises electrolytic polishing treatment; the pretreated aluminum alloy is subjected to anodic oxidation treatment, and an anodic oxidation aluminum alloy is obtained; the preparation method comprises the following steps: preparing a nano-emulsion for hole sealing, wherein the nano-emulsion is prepared from the following components: liquid lithium silicate, gamma-glycidyl ether oxypropyl trimethoxy silane, long-chain alkoxy silane, an anionic surfactant and water; and the anodized aluminum alloy is sequentially immersed into ammonium sebacate and nano-emulsion for hole sealing treatment, and the bright corrosion-resistant film layer on the surface of the aluminum alloy is obtained. According to the method, the corrosion resistance of the aluminum alloy can be improved while the surface brightness is kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present disclosure relate to the field of surface technology, and in particular, to a method for preparing a corrosion-resistant film layer on the surface of an aluminum alloy and the corrosion-resistant film layer on the surface of the aluminum alloy. Background Art

[0002] Anodizing is one of the commonly used surface treatment technologies for aluminum alloy electronic products. The larger the pore size and the thinner the thickness of the anodized film, the higher its surface transparency. However, this will reduce the anti-corrosion ability of the anodized film and cannot block corrosive media such as chloride ions and lactic acid in sweat. Although traditional sealing processes such as boiling water, nickel salts, and chromates can improve corrosion resistance, they still cannot completely block the pores on the surface of high-transparency anodized films, and it is difficult to meet the protection needs of electronic products against sweat corrosion. Although transparent organic coatings prepared on the surface of anodized films by coating or electrophoresis have better corrosion resistance, the realization of high corrosion resistance requires a higher film thickness and will also lead to the loss of surface metal texture. Therefore, the existing anodizing and its sealing processes cannot achieve both bright and transparent aluminum alloy surfaces and corrosion resistance, which seriously affects the stability and user experience of aluminum alloy electronic products.

[0003] In the related art, the surface brightness of aluminum alloy after multiple composite sealing treatments is significantly reduced. By combining anodizing with heat treatment, the heat treatment temperature is above 300°C, which will affect the performance of the aluminum alloy matrix. Summary of the invention

[0004] The purpose of the present disclosure is to provide a method for preparing a corrosion-resistant film layer on the surface of an aluminum alloy and a corrosion-resistant film layer on the surface of an aluminum alloy, thereby overcoming the problem of poor performance of aluminum alloys caused by limitations and defects of related technologies at least to a certain extent.

[0005] According to one aspect of the present disclosure, a method for preparing a corrosion-resistant film layer on the surface of an aluminum alloy is provided, comprising: pre-treating the aluminum alloy to obtain the pre-treated aluminum alloy; the pre-treatment comprises electrolytic polishing; anodizing the pre-treated aluminum alloy to obtain an anodized aluminum alloy; preparing a nanoemulsion for sealing, wherein the components of the nanoemulsion include liquid lithium silicate, γ-glycidyloxypropyltrimethoxysilane, long-chain alkoxysilane, anionic surfactant and water; immersing the anodized aluminum alloy in ammonium sebacate and the nanoemulsion in sequence for sealing to obtain a bright corrosion-resistant film layer on the surface of the aluminum alloy.

[0006] In an exemplary embodiment of the present disclosure, the pretreatment further includes one or more of a degreasing treatment and a neutralization treatment; the temperature of the degreasing treatment is 55-65°C, and the time of the degreasing treatment is 20-40s; the components of the degreasing liquid used in the degreasing treatment include sodium carbonate, sodium phosphate and sodium hydroxide, and the mass ratio of sodium carbonate, sodium phosphate and sodium hydroxide is 1:(0.6-0.9):(0.25-0.5); the time of the neutralization treatment is 10-30s at room temperature, and the component of the neutralization liquid used in the neutralization treatment is 150-200g / L of sulfuric acid; the temperature of the electrolytic polishing treatment is 75-90°C, and the current density of the electrolytic polishing treatment is 4-6A / dm 2 The treatment time of electrolytic polishing treatment is 1~10min; the components of the electrolytic polishing solution used in the electrolytic polishing treatment include phosphoric acid, triethanolamine, tartaric acid, and glycerol. The mass ratio of phosphoric acid, triethanolamine, tartaric acid, and glycerol is 1:(0.15~0.35):(0.1~0.3):(0.5%~1.25%).

[0007] In an exemplary embodiment of the present disclosure, the components of the electrolyte used for anodizing treatment include 150-200 g / L sulfuric acid, 10-50 g / L glycolic acid, and 10-30 g / L triethanolamine; the reaction temperature of the anodizing treatment is 0-10°C.

[0008] In an exemplary embodiment of the present disclosure, the process parameters of the anodizing treatment are: current density 2-5 A / dm 2 , oxidation time is 10~15 min; the thickness of the anodized aluminum alloy is 8~13 μm.

[0009] In an exemplary embodiment of the present disclosure, a nanoemulsion for sealing is prepared, comprising: mixing liquid lithium silicate and water, and performing a first magnetic stirring to obtain a lithium silicate hydrolyzate; mixing the lithium silicate hydrolyzate and γ-glycidyloxypropyltrimethoxysilane, and performing a second magnetic stirring to obtain a mixed solution; and sequentially adding a long-chain alkoxysilane and an anionic surfactant to the mixed solution, and performing a third magnetic stirring to obtain a nanoemulsion.

[0010] In an exemplary embodiment of the present disclosure, the volume ratio of liquid lithium silicate to water is 1:(0.2~1.25); the volume ratio of lithium silicate hydrolyzate to γ-glycidyloxypropyltrimethoxysilane is 1:(0.2~1); the long-chain alkoxysilane accounts for 0.3%~5% of the total mass of the mixed solution, and the anionic surfactant accounts for 0.1%~0.5% of the total mass of the mixed solution; the long-chain alkoxysilane is at least one of dodecyltrimethoxysilane, hexadecyltrimethoxysilane, and octadecyltrimethoxysilane; the anionic surfactant is at least one of sodium dodecylbenzenesulfonate and sodium dodecyl sulfate.

[0011] In an exemplary embodiment of the present disclosure, the concentration of ammonium sebacate is 10 g / L, the sealing temperature is 90-100° C., and the sealing time is 10-30 min.

[0012] In an exemplary embodiment of the present disclosure, the anodized aluminum alloy is immersed in ammonium sebacate and nanoemulsion in sequence for pore sealing treatment, including: immersing the anodized aluminum alloy in ammonium sebacate for pore sealing treatment, immersing the anodized aluminum alloy after the pore sealing treatment in nanoemulsion, and curing after taking out.

[0013] In an exemplary embodiment of the present disclosure, the soaking time is 20 min at room temperature, the curing temperature is 120° C., and the curing time is 1 h.

[0014] According to one aspect of the present disclosure, a corrosion-resistant film layer on the surface of an aluminum alloy is provided. The corrosion-resistant film layer on the surface of an aluminum alloy is prepared according to any one of the above-mentioned methods for preparing the corrosion-resistant film layer on the surface of an aluminum alloy.

[0015] In the technical solution provided in the embodiment of the present disclosure, on the one hand, a two-step sealing process is used to generate aluminoxane insolubles by reacting ammonium sebacate with hydrated aluminum oxide, which can play a better role in sealing micropores than traditional boiling water sealing, and can significantly improve the ability of aluminum alloy electronic products to resist sweat corrosion. At the same time, liquid lithium silicate is used as the water phase, long-chain alkoxysilane with hydrophobicity is used as the oil phase, γ-glycidyl ether oxygen propyl trimethoxysilane KH560 and anionic surfactant are used as composite surfactants to prepare water-in-oil nanoemulsions, which have good film-forming plugging properties and permeability, and the hydrolysis and polycondensation reaction between lithium silicate and organic silane is used to plug the remaining pores and build a dense transparent hydrophobic film on the surface of the oxide film, thereby significantly enhancing the corrosion resistance of the anodized film, improving the performance of the aluminum alloy matrix, and improving the stability and application range of aluminum alloy products. On the other hand, by regulating the anodizing process, the pores of the oxide film generated on its surface are smaller and more uniform without reducing the brightness and transparency of the aluminum alloy surface, which provides the quality of the oxide film and improves the performance of the aluminum alloy.

[0016] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0018] Figure 1 A flow chart schematically shows a method for preparing a corrosion-resistant film layer on the surface of an aluminum alloy in an embodiment of the present disclosure.

[0019] Figure 2 The surface morphology of the anodized aluminum alloy in Example 1 after being sealed with ammonium sebacate and nanoemulsion is schematically shown.

[0020] Figure 3 The polarization curve diagram of the aluminum alloy and its film layer prepared according to Example 1 is schematically shown.

[0021] Figure 4 The surface morphology of the aluminum alloy and its film layer prepared according to Example 1 before and after sweat corrosion is schematically shown.

[0022] Figure 5 Surface morphology of the aluminum alloy and its film layer prepared according to Comparative Example 1 before and after sweat corrosion. DETAILED DESCRIPTION

[0023] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, components, devices, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.

[0024] The terms "a", "an", "the" and "said" used in this specification are used to indicate the presence of one or more elements / components, etc.; the terms "including" and "having" are used to express an open-ended inclusion and mean that there may be additional elements / components, etc. in addition to the listed elements / components, etc.; the terms "first" and "second" etc. are used only as labels and are not intended to limit the quantity of their objects.

[0025] Aluminum alloy is widely used in mobile phones, laptops, cameras and other electronic products due to its light weight, high specific strength, low price, good thermal conductivity and processability, which puts higher requirements on the decorative effect and protective performance of the aluminum alloy surface. Aluminum alloy electronic products will inevitably come into contact with corrosive media such as sweat during use, causing corrosion and fading of the aluminum alloy surface, seriously affecting the aesthetics and service life of electronic products.

[0026] Anodizing is one of the commonly used surface treatment technologies for aluminum alloy electronic products. The larger the pore size and the thinner the thickness of the anodized film, the higher its surface transparency. However, this will reduce the anti-corrosion ability of the anodized film and cannot block corrosive media such as chloride ions and lactic acid in sweat. On the other hand, although traditional sealing processes such as boiling water, nickel salts, and chromates can improve corrosion resistance, they still cannot completely block the pores on the surface of high-transparency anodized films, and it is difficult to meet the protection needs of electronic products against sweat corrosion. Although transparent organic coatings prepared on the surface of anodized films by coating or electrophoresis have better corrosion resistance, the realization of high corrosion resistance requires a higher film thickness and will also lead to the loss of surface metal texture. Therefore, the existing anodizing and its sealing processes cannot achieve both bright and transparent aluminum alloy surfaces and corrosion resistance, which seriously affects the stability and user experience of aluminum alloy electronic products.

[0027] The corrosion resistance of the anodized film has been greatly improved through multiple composite sealing treatments, but the surface brightness of the aluminum alloy has been significantly reduced. The corrosion resistance of the aluminum alloy has been improved by combining anodizing with heat treatment, but the heat treatment temperature of this method is above 300°C, which will affect the mechanical properties of the aluminum alloy matrix.

[0028] In order to solve the above technical problems, the present disclosure provides a method for preparing a corrosion-resistant film layer on the surface of an aluminum alloy, which is used to prepare a bright corrosion-resistant film layer on the surface of an aluminum alloy. Figure 1 As shown in, the method for preparing the corrosion-resistant film layer on the surface of the aluminum alloy mainly includes the following steps: In step S110, the aluminum alloy is pretreated to obtain a pretreated aluminum alloy; the pretreatment includes electrolytic polishing; In step S120, the pretreated aluminum alloy is anodized to obtain an anodized aluminum alloy; In step S130, a nanoemulsion for sealing is prepared, wherein the components of the nanoemulsion include liquid lithium silicate, γ-glycidyloxypropyltrimethoxysilane, long-chain alkoxysilane, anionic surfactant and water; In step S140, the anodized aluminum alloy is immersed in ammonium sebacate and nanoemulsion in sequence for pore sealing treatment to obtain a bright corrosion-resistant film layer on the surface of the aluminum alloy.

[0029] Next, the method for preparing the corrosion-resistant film layer on the surface of the aluminum alloy in the embodiment of the present disclosure is specifically described.

[0030] In step S110, the aluminum alloy is pretreated to obtain a pretreated aluminum alloy; the pretreatment includes electrolytic polishing.

[0031] In the embodiment of the present disclosure, the pretreatment may include an electrolytic polishing treatment. In addition, the pretreatment may also include one or more of a degreasing treatment and a neutralization treatment. The temperature of the degreasing treatment is 60±5°C, i.e. 55~65°C. The time of the degreasing treatment is 20~40s. The components of the degreasing liquid used in the degreasing treatment include sodium carbonate, sodium phosphate and sodium hydroxide, wherein the mass ratio of sodium carbonate, sodium phosphate and sodium hydroxide can be 1:(0.6~0.9):(0.25~0.5). The temperature of the neutralization treatment is room temperature, the time of the neutralization treatment is 10~30s, and the component of the neutralizing liquid used in the neutralization treatment is sulfuric acid 150~200g / L. The temperature of the electrolytic polishing treatment is 75~90°C, and the current density is 4~6A / dm 2 The treatment time is 1 to 10 minutes. The components of the electrolytic polishing solution for electrolytic polishing treatment include phosphoric acid, triethanolamine, tartaric acid, and glycerol, wherein the mass ratio of phosphoric acid, triethanolamine, tartaric acid, and glycerol is 1:(0.15 to 0.35):(0.1 to 0.3):(0.5% to 1.25%). When the pretreatment includes degreasing treatment, neutralization treatment, and electrolytic polishing treatment, the steps of the pretreatment are degreasing treatment, neutralization treatment, and electrolytic polishing treatment in sequence.

[0032] In step S120, the pretreated aluminum alloy is anodized to obtain an anodized aluminum alloy.

[0033] In the embodiment of the present disclosure, the pre-treated aluminum alloy obtained in step S110 is anodized to obtain an anodized aluminum alloy with bright characteristics. The components of the electrolyte used in the anodizing treatment include 150-200 g / L sulfuric acid, 10-50 g / L hydroxyacetic acid, and 10-30 g / L triethanolamine. The reaction temperature of the anodizing treatment is 0-10°C. The process parameters of the anodizing treatment are: current density 2-5 A / dm 2 , oxidation time 10~15 min. Based on the process parameters, anodizing treatment is performed, and the thickness of the prepared anodized aluminum alloy is 8~13 μm. In the embodiment of the present disclosure, by anodizing the pretreated aluminum alloy, the surface of the film layer can be guaranteed to be bright and transparent, and have a certain corrosion resistance. By regulating the anodizing process, the pores of the oxide film generated on the surface of the aluminum alloy can be made smaller and more uniform without reducing the brightness and transparency of the aluminum alloy surface.

[0034] In step S130 , a nanoemulsion for sealing is prepared, wherein the components of the nanoemulsion include liquid lithium silicate, γ-glycidyloxypropyltrimethoxysilane, long-chain alkoxysilane, anionic surfactant and water.

[0035] In the embodiment of the present disclosure, a nanoemulsion for sealing can be configured. The components of the nanoemulsion include liquid lithium silicate, γ-glycidyloxypropyltrimethoxysilane, long-chain alkoxysilane, anionic surfactant and water. The liquid lithium silicate can be liquid lithium silicate with a modulus of 4.8.

[0036] The process of preparing the nanoemulsion includes: mixing liquid lithium silicate with a modulus of 4.8 and water, and performing a first magnetic stirring to obtain a lithium silicate hydrolyzate; mixing the lithium silicate hydrolyzate and γ-glycidyloxypropyltrimethoxysilane, and performing a second magnetic stirring to obtain a mixed solution; and sequentially adding a long-chain alkoxysilane and an anionic surfactant to the mixed solution, and performing a third magnetic stirring to obtain a nanoemulsion.

[0037] During the first magnetic stirring, the volume ratio of the liquid lithium silicate with a modulus of 4.8 and water is 1:(0.2-1.25), that is, the liquid lithium silicate with a modulus of 4.8 and water are mixed in a volume ratio of 1:(0.2-1.25). The first magnetic stirring time can be 30 minutes, or any other suitable time, as long as the two are fully mixed.

[0038] When the lithium silicate hydrolyzate and γ-glycidyloxypropyltrimethoxysilane are mixed, the volume ratio of the lithium silicate hydrolyzate and γ-glycidyloxypropyltrimethoxysilane is 1:(0.2-1), that is, the lithium silicate hydrolyzate and γ-glycidyloxypropyltrimethoxysilane can be mixed in a volume ratio of 1:(0.2-1). The second magnetic stirring time can be longer than the first magnetic stirring time, for example, the second magnetic stirring time can be 2 hours, as long as the two are fully mixed.

[0039] After obtaining the mixed solution, long-chain alkoxysilane and anionic surfactant can be sequentially added to the mixed solution, and a nanoemulsion can be obtained after a third magnetic stirring. The long-chain alkoxysilane is at least one of dodecyltrimethoxysilane, hexadecyltrimethoxysilane, and octadecyltrimethoxysilane. The anionic surfactant is at least one of sodium dodecylbenzenesulfonate and sodium dodecyl sulfate. Among them, the long-chain alkoxysilane accounts for 0.3% to 5% of the total mass of the mixed solution, and the anionic surfactant accounts for 0.1% to 0.5% of the total mass of the mixed solution. The time of the third magnetic stirring can be 2 hours, and can also be determined according to actual needs.

[0040] In step S140, the anodized aluminum alloy is immersed in ammonium sebacate and nanoemulsion in sequence for pore sealing treatment to obtain a bright corrosion-resistant film layer on the surface of the aluminum alloy.

[0041] In the disclosed embodiment, the concentration of ammonium sebacate is 10 g / L, the sealing temperature is 95±5° C., i.e., 90° C. to 100° C., and the sealing time is 10 to 30 min.

[0042] Exemplarily, the process of immersing the anodized aluminum alloy in ammonium sebacate and nanoemulsion for sealing treatment in sequence includes: immersing the anodized aluminum alloy in ammonium sebacate for sealing treatment, immersing the anodized aluminum alloy after the ammonium sebacate sealing treatment in the nanoemulsion, and curing after taking it out. Among them, the immersion time in the nanoemulsion is 20 minutes at room temperature, which can of course be determined according to actual needs. After taking it out, the liquid on the surface can be wiped dry or blown dry, and heated for curing. The curing temperature can be 120°C, and the curing time can be 1h.

[0043] The method in the disclosed embodiment adopts electrolytic polishing treatment to obtain a high-brightness surface; then, by adjusting the anodizing process, the pores of the oxide film generated on the surface of the aluminum alloy are made smaller and more uniform without reducing the brightness and transparency of the aluminum alloy surface; finally, a two-step sealing treatment with ammonium sebacate and nanoemulsion is performed to form a bright and transparent oxide film layer with excellent corrosion resistance.

[0044] By using a two-step sealing process and giving full play to the advantages of each step of sealing, the ability of aluminum alloy electronic products to resist sweat corrosion can be significantly improved. Among them, ammonium sebacate can react with hydrated aluminum oxide to form aluminoxane insolubles, which can play a better role in sealing micropores compared with traditional boiling water sealing. At the same time, liquid lithium silicate is used as the water phase, hydrophobic long-chain alkoxysilane is used as the oil phase, γ-glycidyloxypropyltrimethoxysilane KH560 and anionic surfactant are used as composite surfactants to prepare water-in-oil nanoemulsions. The emulsion has good film-forming plugging and permeability. The hydrolysis and polycondensation reaction between lithium silicate and organic silane is used to plug the remaining pores and build a dense transparent hydrophobic film on the surface of the oxide film, thereby significantly enhancing the corrosion resistance of the anodized film.

[0045] Next, the method for preparing the corrosion-resistant film layer on the surface of the aluminum alloy disclosed in the present invention is specifically described in conjunction with an embodiment.

[0046] Example 1 This embodiment includes the following steps: Step 1. The aluminum alloy is subjected to degreasing treatment, neutralization treatment and electrolytic polishing treatment in sequence to perform pretreatment. The components of the degreasing solution include: sodium carbonate, sodium phosphate and sodium hydroxide, wherein sodium carbonate, sodium phosphate and sodium hydroxide are mixed in a mass ratio of 1:0.6:0.25. The temperature of the degreasing treatment is 60°C, and the time of the degreasing treatment is 40 s. The component of the neutralizing solution used in the neutralization treatment is 200 g / L sulfuric acid, and the time of the neutralization treatment is 30 s at room temperature. The components of the electrolytic polishing solution used in the electrolytic polishing treatment include: phosphoric acid, triethanolamine, tartaric acid, and glycerol. Among them, phosphoric acid, triethanolamine, tartaric acid, and glycerol are mixed in a mass ratio of 1:0.15:0.1:0.5%. The temperature of the electrolytic polishing treatment is 90°C, and the current density is 5 A / dm 2 , the processing time is 5 min.

[0047] Step 2: Anodize the aluminum alloy sample obtained in step 1 after pretreatment. The electrolyte used in the anodizing treatment includes 200 g / L sulfuric acid, 30 g / L hydroxyacetic acid, and 30 g / L triethanolamine. The temperature of the electrolyte is 10°C, that is, the reaction temperature of the anodizing treatment is 10°C. The current density of the anodizing treatment is 2A / dm 2 The anodizing treatment time is 15 min, and a transparent anodized film with a thickness of 12 μm is obtained, thereby obtaining an anodized aluminum alloy with bright characteristics.

[0048] Step 3, prepare nanoemulsion for sealing. First, liquid lithium silicate with a modulus of 4.8 and water are mixed in a volume ratio of 1:0.6, and a lithium silicate hydrolyzate is obtained after magnetic stirring for 30 minutes. Then, the lithium silicate hydrolyzate and γ-glycidyloxypropyltrimethoxysilane KH560 are mixed in a volume ratio of 1:0.4, and a mixed solution is obtained after magnetic stirring for 2 hours. Finally, hexadecyltrimethoxysilane and sodium dodecylbenzenesulfonate are added dropwise to the mixed solution in sequence, wherein hexadecyltrimethoxysilane accounts for 2% of the total mass of the mixed solution, and sodium dodecylbenzenesulfonate accounts for 0.2% of the total mass of the mixed solution. A nanoemulsion is obtained after magnetic stirring for 2 hours.

[0049] Step 4: Soak the anodized aluminum alloy obtained in step 2 in a 10 g / L ammonium sebacate solution for 20 minutes for pore sealing, and the solution temperature is 90-100° C. Then take out the anodized aluminum alloy after the pore sealing treatment, wash it, and then soak it in the nanoemulsion prepared in step 3, soak it at room temperature for 20 minutes, then take it out, and then place it at 120° C. for curing for 1 hour.

[0050] Figure 2 This is a surface morphology of the anodized aluminum alloy prepared in Example 1 and sealed with ammonium sebacate and nanoemulsion. It can be seen from the surface pores of the anodized aluminum alloy that have been completely blocked.

[0051] Figure 3 3 is a polarization curve diagram of the aluminum alloy and its film layer prepared according to Example 1. It can be seen from the figure that the corrosion current density of the anodized film after the ammonium sebacate and nanoemulsion sealing treatment is significantly reduced compared with that before sealing.

[0052] Figure 4 Figure 1 is a surface morphology of the aluminum alloy and its film layer prepared according to Example 1 before and after 48 hours of sweat corrosion. Figure (a) is a surface morphology of the aluminum alloy and its film layer prepared according to Example 1 before corrosion. Figure (b) is a surface morphology of the aluminum alloy and its film layer prepared according to Example 1 after corrosion. Figure 4 From the surface morphology before corrosion shown in Figure (a), it can be seen that after anodizing, the surface of the sample is bright and transparent; Figure 4 From the surface morphology after corrosion shown in Figure (b), it can be seen that after 48 hours of sweat corrosion, there is no discoloration and corrosion points on the surface of the sample. Therefore, the pore sealing treatment with ammonium sebacate and nanoemulsion can effectively resist sweat corrosion.

[0053] Example 2 This embodiment includes the following steps: Step 1. Perform degreasing, neutralization and electrolytic polishing treatments on the aluminum alloy in sequence to perform pretreatment. The components of the degreasing solution used for degreasing treatment include: sodium carbonate, sodium phosphate, and sodium hydroxide, wherein sodium carbonate, sodium phosphate, and sodium hydroxide are mixed in a mass ratio of 1:0.9:0.5. The temperature of the degreasing treatment is 60°C, and the time of the degreasing treatment is 20s. The component of the neutralizing solution used for the neutralization treatment is 180 g / L sulfuric acid, and the time of the neutralization treatment is 10 s at room temperature. The components of the electrolytic polishing solution include phosphoric acid, triethanolamine, tartaric acid, and glycerol, wherein the mass ratio of phosphoric acid, triethanolamine, tartaric acid, and glycerol is 1:0.35:0.3:1.25%. The temperature of the electrolytic polishing treatment is 75°C, and the current density is 6 A / dm 2 , the processing time is 1min.

[0054] Step 2: Anodize the pretreated aluminum alloy obtained in step 1. The electrolyte used in the anodizing treatment includes 150 g / L sulfuric acid, 50 g / L hydroxyacetic acid, and 10 g / L triethanolamine. The temperature of the electrolyte is 0°C, that is, the reaction temperature of the anodizing treatment is 0°C. The current density of the anodizing treatment is 5A / dm 2 , the treatment time is 10min, and a transparent anodized film with a thickness of 13 μm is obtained, thereby obtaining an anodized aluminum alloy with bright characteristics.

[0055] Step 3, prepare nanoemulsion for sealing. First, liquid lithium silicate with a modulus of 4.8 and water are mixed in a volume ratio of 1:0.2, and a lithium silicate hydrolyzate is obtained after magnetic stirring for 30 minutes. Then, the lithium silicate hydrolyzate and γ-glycidyloxypropyltrimethoxysilane KH560 are mixed in a volume ratio of 1:0.2, and a mixed solution is obtained after magnetic stirring for 2 hours. Finally, hexadecyltrimethoxysilane and sodium dodecylbenzenesulfonate are added dropwise to the mixed solution in sequence, wherein octadecyltrimethoxysilane accounts for 0.3% of the total mass of the mixed solution, and sodium dodecyl sulfate accounts for 0.1% of the total mass of the mixed solution. After magnetic stirring for 2 hours, a nanoemulsion is obtained.

[0056] Step 4: Soak the anodized aluminum alloy obtained in step 2 in a 10 g / L ammonium sebacate solution for 30 min at a solution temperature of 90-100° C. Then take out the sealed anodized aluminum alloy, wash it, and soak it in the nanoemulsion again. Take it out after soaking at room temperature for 20 min, and then place it at 120° C. for curing for 1 h.

[0057] Example 3 This embodiment includes the following steps: Step 1. The aluminum alloy is degreased, neutralized and electropolished in sequence for pretreatment. The components of the degreasing solution used in the degreasing treatment include: sodium carbonate, sodium phosphate, sodium hydroxide, and the mass ratio of sodium carbonate, sodium phosphate and sodium hydroxide is 1:0.75:0.375. The temperature of the degreasing treatment is 60°C, and the treatment time is 30 s. The component of the neutralizing solution used in the neutralization treatment is 150 g / L sulfuric acid, and the neutralization treatment time is 20 s at room temperature. The components of the electrolytic polishing solution used in the electrolytic polishing treatment include phosphoric acid, triethanolamine, tartaric acid, and glycerol, wherein the mass ratio of phosphoric acid, triethanolamine, tartaric acid, and glycerol is 1:0.2:0.2:1%. The temperature of the electrolytic polishing treatment is 80°C, and the current density is 4A / dm 2 , the processing time is 10min.

[0058] Step 2: Anodize the aluminum alloy sample obtained in step 1 after pretreatment. The electrolyte used in the anodizing treatment includes 180 g / L sulfuric acid, 10 g / L hydroxyacetic acid, and 20 g / L triethanolamine. The temperature of the electrolyte is 5°C, that is, the reaction temperature of the anodizing treatment is 5°C. The current density of the anodizing treatment is 4 A / dm 2 , the processing time is 13 min, and a transparent anodized film with a thickness of 10 μm is obtained, thereby obtaining an anodized aluminum alloy with bright characteristics.

[0059] Step 3, prepare nanoemulsion for sealing. First, liquid lithium silicate with a modulus of 4.8 and water are mixed in a volume ratio of 1:1.25, and a lithium silicate hydrolyzate is obtained after magnetic stirring for 30 minutes. Then, the lithium silicate hydrolyzate and γ-glycidyloxypropyltrimethoxysilane KH560 are mixed in a volume ratio of 1:1, and a mixed solution is obtained after magnetic stirring for 2 hours. Finally, hexadecyltrimethoxysilane and sodium dodecylbenzenesulfonate are added dropwise to the mixed solution in sequence, wherein dodecyltrimethoxysilane accounts for 5% of the total mass of the mixed solution, and sodium dodecyl sulfate accounts for 0.5% of the total mass of the mixed solution. After magnetic stirring for 2 hours, a nanoemulsion is obtained.

[0060] Step 4: Soak the anodized aluminum alloy obtained in step 2 in a 10 g / L ammonium sebacate solution for 10 min at a solution temperature of 90-100° C. Then take out the sealed anodized aluminum alloy, wash it, and then soak it in the prepared nanoemulsion, soak it at room temperature for 20 min, then take it out and place it at 120° C. for curing for 1 h.

[0061] Example 4 This embodiment includes the following steps: Step 1. The aluminum alloy is degreased, neutralized and electropolished in sequence for pretreatment. The degreasing solution used in the degreasing treatment includes sodium carbonate, sodium phosphate and sodium hydroxide, and the mass ratio of sodium carbonate, sodium phosphate and sodium hydroxide is 1:0.7:0.3. The temperature of the degreasing treatment is 60°C, and the treatment time is 25 s. The component of the neutralizing solution used in the neutralization treatment is 160 g / L sulfuric acid, and the neutralization treatment time is 15 s at room temperature. The components of the electropolishing solution used in the electropolishing treatment include phosphoric acid, triethanolamine, tartaric acid and glycerol, and the mass ratio of phosphoric acid, triethanolamine, tartaric acid and glycerol is 1:0.3:0.2:0.75%. The temperature of the electropolishing treatment is 85°C, and the current density is 4.5 A / dm 2 , the processing time is 8min.

[0062] Step 2: Anodize the pretreated aluminum alloy obtained in step 1. The electrolyte used in the anodizing treatment includes 160 g / L sulfuric acid, 20 g / L hydroxyacetic acid, and 15 g / L triethanolamine. The temperature of the electrolyte is 3°C, that is, the reaction temperature of the anodizing treatment is 3°C. The current density of the anodizing treatment is 3A / dm 2 The treatment time is 12 min, and a transparent anodized film with a thickness of 8 μm is obtained, thereby obtaining an anodized aluminum alloy with bright characteristics.

[0063] Step 3, prepare nanoemulsion for sealing. First, liquid lithium silicate with a modulus of 4.8 and water are mixed in a volume ratio of 1:0.5, and a lithium silicate hydrolyzate is obtained after magnetic stirring for 30 minutes. Then, the lithium silicate hydrolyzate and γ-glycidyloxypropyltrimethoxysilane KH560 are mixed in a volume ratio of 1:0.8, and a mixed solution is obtained after magnetic stirring for 2 hours. Finally, hexadecyltrimethoxysilane and sodium dodecylbenzenesulfonate are added dropwise to the mixed solution in sequence, wherein hexadecyltrimethoxysilane accounts for 3% of the total mass of the mixed solution, and sodium dodecylbenzenesulfonate accounts for 0.3% of the total mass of the mixed solution. After magnetic stirring for 2 hours, a nanoemulsion is obtained.

[0064] Step 4: Soak the anodized aluminum alloy obtained in step 2 in a 10 g / L ammonium sebacate solution for 15 min at a solution temperature of 95±5°C to perform pore sealing. Then, take out the sealed anodized aluminum alloy, clean it, and then soak it in the prepared nanoemulsion. After soaking at room temperature for 20 min, take it out and place it at 120°C for curing for 1 h.

[0065] Example 5 This embodiment includes the following steps: Step 1. The aluminum alloy is degreased, neutralized and electropolished in sequence for pretreatment. The mass ratio of sodium carbonate, sodium phosphate and sodium hydroxide in the degreasing solution used for degreasing is 1:0.8:0.4. The temperature of the degreasing treatment is 60°C, and the treatment time is 35 s. The component of the neutralization solution used in the neutralization treatment is 190 g / L sulfuric acid, and the neutralization treatment time is 25 s at room temperature. The components of the electropolishing solution used for electropolishing treatment include: phosphoric acid, triethanolamine, tartaric acid, and glycerol, wherein the mass ratio of phosphoric acid, triethanolamine, tartaric acid, and glycerol is 1:0.25:0.15:0.9%. The temperature of the electropolishing treatment is 90°C, and the current density is 5.5 A / dm 2 , the processing time is 3 min.

[0066] Step 2: Anodize the aluminum alloy sample obtained in step 1 after pretreatment. The electrolyte used in the anodizing treatment includes 170 g / L sulfuric acid, 40 g / L hydroxyacetic acid, and 25 g / L triethanolamine. The temperature of the electrolyte is 8°C, that is, the reaction temperature of the anodizing treatment is 8°C. The current density of the anodizing treatment is 2.5 A / dm 2 , the processing time is 11 min, and a transparent anodized film with a thickness of 9 μm is obtained, thereby obtaining an anodized aluminum alloy with bright characteristics.

[0067] Step 3: Prepare nanoemulsion for sealing. First, liquid lithium silicate with a modulus of 4.8 and water are mixed in a volume ratio of 1:1, and a lithium silicate hydrolyzate is obtained after magnetic stirring for 30 minutes. Then, the lithium silicate hydrolyzate and γ-glycidyloxypropyltrimethoxysilane KH560 are mixed in a volume ratio of 1:0.5, and a mixed solution is obtained after magnetic stirring for 2 hours. Finally, hexadecyltrimethoxysilane and sodium dodecylbenzenesulfonate are added dropwise to the mixed solution in sequence, wherein hexadecyltrimethoxysilane accounts for 1% of the total mass of the mixed solution, and sodium dodecylbenzenesulfonate accounts for 0.4% of the total mass of the mixed solution. A nanoemulsion is obtained after magnetic stirring for 2 hours.

[0068] Step 4: Soak the anodized aluminum alloy obtained in step 2 in a 10 g / L ammonium sebacate solution for 25 min at a solution temperature of 90-100° C. Then take out the sealed anodized aluminum alloy, wash it, and then soak it in the nanoemulsion prepared in step 3. Soak it at room temperature for 20 min, then take it out and place it at 120° C. for curing for 1 h.

[0069] Comparative Example 1 Compared with Example 1, the process of anodizing treatment in this comparative example is different, and there is no need to perform pore sealing treatment using ammonium sebacate and nanoemulsion. The specific process is as follows: Step 1: Pre-treat the aluminum alloy by degreasing, neutralizing, and electrolytic polishing.

[0070] Step 2: Prepare a transparent anodized film on the surface of the aluminum alloy by conventional anodizing. The electrolyte used is 200 g / L sulfuric acid and the temperature of the electrolyte is 10°C, that is, the reaction temperature of the anodizing treatment is 10°C. The current density of the anodizing treatment is 2 A / dm 2 The treatment time was 15 min, and a transparent anodized film with a thickness of 13 μm was obtained. The anodized sample was placed in 95°C distilled water for 30 min, taken out and blown dry to complete the boiling water sealing.

[0071] Figure 5 Figure 1 is a surface morphology of the aluminum alloy film prepared according to Comparative Example 1 before and after 48 hours of sweat corrosion, wherein Figure (a) is a surface morphology of the aluminum alloy film prepared according to Comparative Example 1, and Figure (b) is a surface morphology of the aluminum alloy film prepared in Comparative Example 1 after sweat corrosion. Figure 5 The aluminum alloy film layer prepared according to Comparative Example 1 shown in Figure (a) shows that Figure 4 The surface of the film layer prepared by anodizing treatment in Example 1 shown in the middle figure (a) is slightly yellowish. Figure 5The surface morphology of the aluminum alloy film layer prepared in Comparative Example 1 after sweat corrosion as shown in the middle figure (b) shows that after 48 hours of sweat corrosion, the surface of the aluminum alloy film layer prepared in Comparative Example 1 becomes darker and a large number of corrosion spots appear, and the anti-sweat corrosion effect is poor.

[0072] In summary, the technical solution in the disclosed embodiment, compared with the traditional single sealing technology, utilizes a two-step sealing process to give full play to the advantages of each step of sealing, and can significantly improve the ability of aluminum alloy electronic products to resist sweat corrosion. Among them, ammonium sebacate can react with hydrated aluminum oxide to form aluminoxane insolubles, which can play a better role in sealing micropores than traditional boiling water sealing. At the same time, liquid lithium silicate is used as the water phase, a long-chain alkoxysilane with hydrophobicity is used as the oil phase, and a silane coupling agent (γ-glycidyl ether oxypropyl trimethoxysilane KH560) and anionic surfactant are used as composite surfactants to prepare a water-in-oil nanoemulsion. The emulsion has good film-forming plugging and permeability, and utilizes the hydrolysis and polycondensation reaction between lithium silicate and organic silane to plug the remaining pores and build a dense transparent hydrophobic film on the surface of the oxide film, thereby significantly enhancing the corrosion resistance of the anodized film.

[0073] In the embodiment of the present disclosure, there is also provided an aluminum alloy surface corrosion-resistant film layer prepared according to the method of step S110 to step S140. The anodized film prepared in the embodiment of the present disclosure has good sweat corrosion resistance while maintaining a bright and transparent appearance and not significantly increasing the thickness of the film layer, thereby achieving both aesthetics and performance of aluminum alloy electronic products. The entire process has no heavy metal ion emissions, is green and environmentally friendly, and is particularly suitable for surface protection of electronic products.

[0074] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.

[0075] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.

[0076] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.

Claims

1. A method for preparing a corrosion-resistant film on an aluminum alloy surface, characterized in that: include: Pre-treating the aluminum alloy to obtain a pre-treated aluminum alloy; The pretreatment includes electrolytic polishing; The pretreated aluminum alloy is subjected to anodizing treatment to obtain an anodized aluminum alloy; Preparing a nanoemulsion for sealing, wherein the components of the nanoemulsion include liquid lithium silicate, γ-glycidyloxypropyltrimethoxysilane, long-chain alkoxysilane, anionic surfactant and water; The anodized aluminum alloy is sequentially immersed in ammonium sebacate and the nanoemulsion for pore sealing treatment to obtain a bright corrosion-resistant film layer on the surface of the aluminum alloy.

2. The method for preparing a corrosion-resistant film layer on an aluminum alloy surface according to claim 1, characterized in that: The pretreatment also includes one or more of a degreasing treatment and a neutralization treatment; The temperature of the degreasing treatment is 55-65° C., and the time of the degreasing treatment is 20-40 seconds. The components of the degreasing liquid used in the degreasing treatment include sodium carbonate, sodium phosphate and sodium hydroxide, and the mass ratio of the sodium carbonate, the sodium phosphate and the sodium hydroxide is 1:(0.6-0.9):(0.25-0.5); The neutralization treatment time is 10-30s at room temperature, and the component of the neutralization solution used in the neutralization treatment is 150-200g / L of sulfuric acid; The temperature of the electrolytic polishing treatment is 75-90°C, and the current density of the electrolytic polishing treatment is 4-6A / dm 2 The electrolytic polishing treatment time is 1 to 10 minutes; The components of the electrolytic polishing solution used in the electrolytic polishing treatment include phosphoric acid, triethanolamine, tartaric acid, and glycerol. The mass ratio of the phosphoric acid, triethanolamine, tartaric acid, and glycerol is 1:(0.15~0.35):(0.1~0.3):(0.5%~1.25%).

3. The method for preparing the corrosion-resistant film layer on the surface of aluminum alloy according to claim 1, characterized in that: The components of the electrolyte used in the anodizing treatment include 150-200 g / L sulfuric acid, 10-50 g / L glycolic acid, and 10-30 g / L triethanolamine; the reaction temperature of the anodizing treatment is 0-10°C.

4. The method for preparing a corrosion-resistant film layer on the surface of an aluminum alloy according to claim 1, characterized in that: The process parameters of the anodizing treatment are: current density 2~5 A / dm 2 , oxidation time is 10~15 min; the thickness of the anodized aluminum alloy is 8~13 μm.

5. The method for preparing a corrosion-resistant film layer on the surface of an aluminum alloy according to claim 1, characterized in that: The method for preparing the nanoemulsion for sealing the pores comprises: Mixing the liquid lithium silicate and water, and performing a first magnetic stirring to obtain a lithium silicate hydrolyzate; The lithium silicate hydrolyzate and γ-glycidyloxypropyltrimethoxysilane are mixed, and a second magnetic stirring is performed to obtain a mixed solution; Long-chain alkoxysilane and anionic surfactant are sequentially added dropwise to the mixed solution, and the nanoemulsion is obtained after the third magnetic stirring.

6. The method for preparing a corrosion-resistant film layer on the surface of an aluminum alloy according to claim 5, characterized in that: The volume ratio of the liquid lithium silicate to water is 1:(0.2~1.25); the volume ratio of the lithium silicate hydrolyzate to γ-glycidyloxypropyltrimethoxysilane is 1:(0.2~1); the long-chain alkoxysilane accounts for 0.3%~5% of the total mass of the mixed solution, and the anionic surfactant accounts for 0.1%~0.5% of the total mass of the mixed solution; the long-chain alkoxysilane is at least one of dodecyltrimethoxysilane, hexadecyltrimethoxysilane, and octadecyltrimethoxysilane; the anionic surfactant is at least one of sodium dodecylbenzenesulfonate and sodium dodecyl sulfate.

7. The method for preparing a corrosion-resistant film layer on the surface of an aluminum alloy according to claim 1, characterized in that: The concentration of the ammonium sebacate is 10 g / L, the sealing temperature is 90-100° C., and the sealing time is 10-30 min.

8. The method for preparing a corrosion-resistant film layer on the surface of an aluminum alloy according to claim 1, characterized in that: The anodized aluminum alloy is sequentially immersed in ammonium sebacate and the nanoemulsion for pore sealing treatment, comprising: The anodized aluminum alloy is immersed in ammonium sebacate for pore sealing, and the anodized aluminum alloy after the pore sealing is immersed in nano-emulsion, and then taken out for curing.

9. The method for preparing a corrosion-resistant film layer on the surface of an aluminum alloy according to claim 8, characterized in that: The immersion time is 20 min at room temperature, the curing temperature is 120° C., and the curing time is 1 h.

10. A corrosion-resistant film layer on the surface of an aluminum alloy, characterized in that: The corrosion-resistant film layer on the surface of the aluminum alloy is prepared according to the method for preparing the corrosion-resistant film layer on the surface of the aluminum alloy according to any one of claims 1-9.

Citation Information

Patent Citations

  • Self-repairing confining liquid and method for confining aluminium alloy anodic oxide film by using the same

    CN101792921A

  • Aluminum alloy anodic oxide film nickel-free sealant for harsh environment and preparation method thereof

    CN105200484A

  • Curable film-forming compositions containing lithium silicates as corrosion inhibitors and multilayer coated metal substrates

    CN107709483A

  • Aluminum profile oxidization post-treatment liquid

    CN108315798A

  • Aluminum and aluminum alloy anodic oxidation aftertreatment liquid and preparation method thereof

    CN109056028A